Psychometric properties of the Short Form-8 Health Survey (SF-8) among diabetes and non-diabetes Iranian older people - Shamsedin Namjoo; Masoud Mirzaei; Mahshid Foroughan; Gholamreza Ghaedamini Harouni (Tabriz University of Medical Sciences, 2021)
Background: The current study aimed to evaluate the psychometric properties of the Persian version of the 8-item Short-Form Health Survey (SF-8). For this purpose, we examined a large sample of the older adult in two different groups with and without diabetes using the YazdHealth Study (YaHS) data. Methods: Using a two-stage cluster random sampling method, 1901 older adults were recruited, according to the World Health Organization (WHO) STEPwise approach to surveillance(STEPS) guidelines. To test the scale's reliability, the internal consistency and test-retest methods were applied. The convergent validity of the entire questionnaire was evaluated by the average variance extracted (AVE) and composite reliability (CR) for each subscale. An independent samples t-test was used to assess the demographic differences between the study groups. Results: The Cronbach's alpha coefficient for the subscales of SF-8 were measured to range between 0.85 and 0.79 (physical & mental health). The test-retest reliability coefficient of the physical component summary (PCS) and (0.97) and mental component summary (MCS) (0.98)indicated the appropriate reliability of the SF-8. The CFA-concerned results indicated that the the2‐factor model presented a good fit to the data for the explored diabetes and non-diabetes groups, as well as the total research participants [goodness of fit index (GFI)=0.99, comparative fit index (CFI)=0.992, normed fit index (NFI)=0.99, incremental fit index (IFI)=0.992, root mean square error of approximation (RMSEA)=0.056]. Values >0.5 and >0.7 for AVE and CR indicated the evidence of the convergent validity of the SF-8.Conclusion: The present study was the first attempt to confirm the traditional 2-factor structure of SF-8 among a large sample of Iranian older individuals. The obtained results suggested that the Persian version of the SF-8 is a reliable and valid tool for measuring health-related quality of life (HRQoL) among Iranian older adults (including the older adult with & without diabetes).